Implementation of Winnowing Algorithm for Document Plagiarism Detection - Nurissaidah Ulinnuha; Muhammad Thohir; Dian Candra Rini Novitasari; Ahmad Hanif Asyhar; Ahmad Zaenal Arifin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Plagiarism prevention efforts are being evolved in various sector. Designing and developing plagiarism checker applications is the purpose of this paper. Specifically by knowing the percentage of similarity between the original document and the test document. Winnowing algorithm is used because it can detect plagiarism in documents up to sub-section of the document. In this paper using three validators consisting of computational mathematicians, software engineering experts, and users to test the feasibility of the application. Experiment using several scenarios, the result of the equation using winnowing algorithm is 90.12%.